Habitat structural complexity explains patterns of feral cat and dingo occurrence in monsoonal Australia. Issue 7 (13th April 2020) - Stobo‐Wilson, Alyson M.; Stokeld, Danielle; Einoder, Luke D.; Davies, Hugh F.; Fisher, Alaric; Hill, Brydie M.; Mahney, Terry; Murphy, Brett P.; Stevens, Alys; Woinarski, John C. Z.; Rangers, Bawinanga; Warddeken Rangers,; et al.
Abstract: Aim: An interaction between reduced habitat structural complexity and predation by feral cats ( Felis catus ) has been hypothesized as the primary driver of mammal decline in northern Australia. However, we have a limited understanding of the drivers of the distribution and abundance of feral cats at a landscape scale, including whether the occurrence of a top predator, the dingo ( Canis familiaris [dingo]), limits feral cat populations. We modelled feral cat and dingo site occurrence, to provide the first broad‐scale assessment of their distributional patterns and co‐occurrence within monsoonal Australia. Location: About 370, 000 km 2 of monsoonal area in the Northern Territory. Methods: We surveyed 376 sites using camera traps. We used single‐ and two‐species occupancy models to investigate feral cat and dingo site occurrence and the influence of dingoes on feral cat occupancy. We included predictor variables that relate to hypotheses of predator occurrence, including both environmental and disturbance‐related variables. Results: Feral cat occurrence and dingo occurrence were best predicted by indices of habitat structural complexity; feral cat occurrence declined with increasing productivity, except in areas of relatively high fire activity (fire frequency and extent), and dingo occurrence declined with terrain ruggedness. We found no evidence that dingoes are spatially limiting feral cat occurrence. Main conclusions: Our findings suggest the protection and enhancement of habitat structural complexity at both the local and landscape scale could enable conservation managers to reduce the exposure of small‐ and medium‐sized mammals to feral cats and dingoes. This can most likely be achieved through improved fire and feral herbivore management, which is a more feasible management option than lethal predator control.